What Role Do Peers Play in Adolescent Dating? Insights From Adolescents With a History of Dating Violence. (February 2017) - Baker, Charlene K.
Prior research suggests that peers are important to adolescent dating experiences. However, questions remain about the role peers play in adolescent relationships, including dating violence. To fill this gap, eight sex-specific focus groups were conducted with 39 high school–aged teens, all of whom had experienced prior relationship problems. Participants described how peers helped them initiate dating relationships, but once in the relationship, peers would spread rumors and create dramas that led to jealousy, discord, and violence between the couple. Prevention programs should focus on cultivating peers as helpful bystanders and counteracting peer actions that lead to dating violence.